Migratory Metrics of Wound Healing: A Quantification Approach for in vitro Scratch Assays - Varankar, Sagar S.; Bapat, Sharmila A. (Frontiers in Oncology, 2018)
Metastatic dissemination generates an aggressive disease facilitated by enhanced migratory and invasive properties. Experimental approaches employ several in vitro and in vivo assays toward quantification of these functionalities. In vitro assessments of cell motility often employ endpoint assays that rely on the global efficacy of wound closure and thwart quantification of migratory phenotypes observed during metastatic dissemination. Recent studies highlight the distinct signatures associated with individual vs. collective cell migration and necessitate the incorporation of these modalities into routine analyses. Advances in live cell imaging that permit real-time visualization of pathophysiological processes can be employed toward elucidating phenotypic plasticity associated with cell migration to overcome caveats inherent to end-point assays. Herein, we corroborate live cell imaging with the in vitro scratch assay toward quantification of migratory modalities in transformed cells. Our protocol describes a step-by-step approach for live cell setup of the scratch assay, and details analyses employed toward definition of three quantitative metrics viz., displacement, velocity and number of nearest neighbors. The current protocol (from scratch induction to data acquisition) is implemented for ~30 h and provides global/single-cell resolution of migratory phenotypes as opposed to the endpoint assays. Routine application of this protocol in cancer biology can aid the design of therapeutic regimes targeting specific migratory modalities and significantly contribute to the dissection of associated molecular networks.